2018
DOI: 10.5696/2156-9614-8.19.180914
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Hepatitis B Virus and Compliance to Standard Safety Precautions among Scavengers in Ilorin Metropolis, Kwara State, Nigeria

Abstract: Background.Scavengers, due to the nature of their work, are at risk of various occupational hazards while sorting for materials for recycling and sale. They are exposed to blood borne infections such as hepatitis B virus (HBV) infection from injuries from sharps and contact with discarded materials due to non-compliance with standard precautions.Objective.The present study assessed the prevalence of HBV and compliance with safety precautions among scavengers in Ilorin Metropolis, Kwara State, Nigeria.Methods.A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
2
7
2
2
Order By: Relevance
“…Kwara south followed with seven (7) hepatitis B positive incidences and Kwara north has the least cases of hepatitis B positivity with six (6) cases. This is in agreement with the work of Yusuf et al [36] which also shows a high hepatitis B positivity among scavengers in Ilorin metropolis. Also, the result corroborates Sawyerr et al [2] in their findings that revealed higher incidence of hepatitis B virus among wastes scavengers in comparison with the municipal street sweepers.…”
Section: Discussionsupporting
confidence: 93%
“…Kwara south followed with seven (7) hepatitis B positive incidences and Kwara north has the least cases of hepatitis B positivity with six (6) cases. This is in agreement with the work of Yusuf et al [36] which also shows a high hepatitis B positivity among scavengers in Ilorin metropolis. Also, the result corroborates Sawyerr et al [2] in their findings that revealed higher incidence of hepatitis B virus among wastes scavengers in comparison with the municipal street sweepers.…”
Section: Discussionsupporting
confidence: 93%
“…None of them used rubber boots while working at the dumpsites. There is similarity between findings in this study and findings by Yusuf et al [18] who made the following findings that majority of the scavengers did not have knowledge of personal protective equipment and did not use the necessary standard precautions necessary to prevent the occurrence of health problems while working. Conversely, Gebremedhin et al [10] reported high level of practice of safety precaution, most of the respondents adhered to the various safety precautions as well as use required personal protective equipment including rubber boots, mouth and nose masks, protective gloves amongst others.…”
Section: Resultssupporting
confidence: 85%
“…Only few of the participants in that study used protective gloves and booths (Awopetu et al, 2014). Another study conducted by [18] among dumpsite waste managers and scavengers in Lagos, Nigeria reported a similar finding that (4.0%) of the respondents used aprons and nose covers indicating poor practice of safety measures. However, none of them used protective gloves nor rubber boots.…”
Section: Resultsmentioning
confidence: 61%
“…Studies conducted in Nigeria 22 , Pakistan 23 and Central Greece 24 showed HBV prevalence rates in waste pickers of 17.4%, 18.8% and 23.0%, respectively. Regarding the potential causes of hepatitis B infection in waste pickers, the papers suggested: handling waste with bare hands and feet; inadequate and precarious waste disposal system; poor vaccination status; handling of piercing-cutting instruments (biomedical waste); no use of personal protective equipment; health insurance; unavailability of health education material.…”
Section: Discussionmentioning
confidence: 99%